NEED ANALYSIS IN LEARNING ENGLISH FOR ACCOUNTING STUDENTS IN ISLAMIC UNIVERSITY - Musdalifah; Muhammad Fahri Jaya Sudding; Ashabul Kahfi Susanto; Citra Dwi Safitri; Andi Kamariah (J-Shelves of Indragiri (JSI), 2025)
The lack of English learning materials tailored to the specific academic and professional needs of accounting students in Islamic universities presents a challenge in preparing students for the global workplace. This study aims to identify the English learning needs of accounting students at an Islamic university in order to develop relevant and effective learning materials. Data were collected using a google Form questionnaire distributed to students, English lecturers, accounting lecturers and graduates. The data were analyzed using a descriptive qualitative approach. The findings indicate that all four language skills (listening, speaking, reading, and writing), along with language components such as grammar and vocabulary, are considered important by respondents. The students preferred teaching methods that include discussion, exercise, demonstrations, role-play, vocabulary drills, group work, and video-based learning. Regarding assessment, the majority of students favored restricted response tests, written tests, matching items, performance-based tests, and multiple-choice questions. In addition to general English topics, students express the need to learn terminology related to Islamic Accounting. Essential language functions identified include self-introduction, participating in meetings, and communicating in professional contexts such as client interactions and academic conferences. These findings can be used to produce English learning material tailored to specific needs of accounting students in Islamic higher education institutions